Pengaruh Lingkungan Kerja dan Motivasi terhadap Kinerja Karyawan PT. Alfaria Trijaya TBK Parung Bogor - Zega, Imam Krisna Anjellina (Lensa Ilmiah: Jurnal Manajemen dan Sumberdaya, 2023)
The purpose of this study was to determine the effect of the work environment and motivation on employee performance at PT. Alfaria Trijaya Tbk Parung Bogor Head Office either partially or simultaneously. The method used is a quantitative method with a assosiative descriptive approach. The sampling technique used is Non-Probability sampling using a sample of 50 respondents. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, analysis of the coefficient of determination and hypothesis testing Work Environment and Motivation have a significant effect on Employee Performance with the regression equation Y = 1.964 + 0.574 X1 + 0.388 X2 . The correlation value is 0.967. This means that the independent variable and the dependent variable have a very strong relationship with a coefficient of determination of 93.5%. while the remaining 29.6% was influenced by other factors. Hypothesis testing obtained Fcount 336.730 > Ftable 3.19. Thus H0 is rejected and H3 is accepted. This means that there is a significant simultaneous influence between the Work Environment and Motivation on Employee Performance at PT Alfaria Trijaya Tbk Parung Bogor Head Office.